On the consistency of Quine’s doctrine - Nélida Gentile (Filosofia Unisinos)
Through his critique of traditional semantics, his attack on the “myth of a museum”, Quine established different relationships between the theses of the inscrutability of reference, the indeterminacy of translation and the underdetermination of theories by evidence. The elucidation of Quine’s ideas has produced many philosophic discussions. In this vein, Roth offers a reconstruction of Quine’s views and rejects some of the logic relationships mentioned above, for, according to Roth, Quine holds an inconsistent doctrine of radical translation. The purpose of this paper is to evaluate the consistency of Quine’s doctrine of radical translation. It argues that if we pay attention to the evolution of his thinking, on the one hand, and to the differences between purely logical remarks and matters of fact possibilities, on the other hand, it is not possible to think that Quine has incurred in intolerable contradictions. Also, from a pragmatic point of view, it argues that in the course of his extended career Quine adopted an increasingly radical empiricism. Keywords: holism, Quine, reference, meaning, underdetermination, translation.